WIKIPEDIA’S ENLIGHTENMENT PROBLEM: DECOLONIZING WESTERN EPISTEMOLOGIES THROUGH CRITICAL OPEN EDUCATION PRACTICES - Vetter, Matthew A.; McDowell, Zachary J. (AoIR Selected Papers of Internet Research, 2023)
Although Wikipedia uniquely challenges the boundaries of the encyclopedic genre in terms of collaboration, technology, authority, and knowledge production, it remains an encyclopedia, an epistemological method and forum that carries with it the ideological traces and functions of Enlightenment print culture. Such print culture manifests itself most visibly in the policy of verifiability. Although verifiability ensures that editors support their claims with a reliable, published source, a concern emerges when we recognize that verifiability and reliability are typically only granted to written, published sources. Consequently, Wikipedia omits a tremendous amount of human knowledge, especially from cultures without a (privileged) history of print culture. Cultures and regions representing the global south, indigenous cultures and peoples, and other types of knowledge where an oral culture plays a large part in the transmission and curation of knowledge are simply not accounted for. Wikipedia’s vision (somewhat paradoxically) remains hindered by its adherence to colonialist epistemologies that continue to define the genre. This paper articulates Wikipedia’s colonialist epistemology problem by 1) reviewing the core content policies that prohibit alternative and indigenous sources of knowledge, especially verifiability and notability policies and 2) focusing on direct examples of the encyclopedia’s inability to represent indigenous knowledge. In linking contemporary Wikipedia policies to colonialist ideologies, we also trace the encyclopedia genre from its western predecessor, showcasing how Wikipedia continues this tradition via its own techno-optimistic rhetoric. Finally, we discuss failed attempts to address the issue of indigenous knowledge within Wikipedia, and make recommendations for its future.